2015
DOI: 10.4067/s0034-98872015000900016
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan disorder syndrome (MODS) in an octagenarian suggests mitochondrial disorder

Abstract: Non -syndromic, multi-organ mitochondrial disorders (MIDs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Already Leber himself reported that some of his LHON patients presented with headache, vertigo, epilepsy, mental impairment, nystagmus, tremor, areflexia, loss of sphincter control, pyramidal tract disease, ataxia, or sensory disturbances 35. Further evidence was provided later for the fact that LHON is not exclusively an ophthalmologic disorder but rather a multisystem disease with predominant affection of the eyes (mitochondrial multiorgan disorder syndrome) 36,37. There are also indications that primary LHON mutations may not manifest phenotypically with ophthalmologic disease but with dominant organ involvement other than the eyes 30,38,39.…”
Section: Discussionmentioning
confidence: 99%
“…Already Leber himself reported that some of his LHON patients presented with headache, vertigo, epilepsy, mental impairment, nystagmus, tremor, areflexia, loss of sphincter control, pyramidal tract disease, ataxia, or sensory disturbances 35. Further evidence was provided later for the fact that LHON is not exclusively an ophthalmologic disorder but rather a multisystem disease with predominant affection of the eyes (mitochondrial multiorgan disorder syndrome) 36,37. There are also indications that primary LHON mutations may not manifest phenotypically with ophthalmologic disease but with dominant organ involvement other than the eyes 30,38,39.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Often, only a single organ is initially affected and other organs are consecutively affected after long periods of time. 19 There is no consistent pattern of organ involvement and no regular sequence among the organs which are affected. Factors which drive the pattern of organ involvement and the speed of progression may include the type of mutation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…133 More frequently, basal ganglia calcification can be found in nsMIDs than in specific MIDs. 134 Basal ganglia calcification may even occur in pediatric patients with MELAS. 135,136 In single cases, basal ganglia calcification was associated with generalized dystonia.…”
Section: Basal Ganglia Calcificationmentioning
confidence: 99%